Patagonian broken foreland and related synorogenic rifting: The origin of the Chubut Group Basin - Gianni, Guido Martin (2015)
The Central Patagonia is characterized by prominent continental deposits that belong to the Cretaceous Chubut Group Basin, whose tectonic setting remains controversial. It has been interpreted as a foreland basin, an extensional basin and even as a sag stage of a rift event. Related deposits outcrop as part of the Patagonian broken foreland, east of the Patagonian Andes. Particulary, the San Bernardo fold and thrust belt, between 42° and 48°S, as the main sector of the broken foreland, constitutes a NNW-trending intraplate belt located 450. km away from the trench. Coincidentally, at these latitudes, 1200. km east of the trench, intraplate deformation has caused tectonic inversion of Mesozoic basins presently located at the Atlantic offshore area. Additionally, at the San Jorge Gulf area this orogenic system interferes with a conspicuous E-W extensional system, transversally disposed to the Andean strike, mainly active between the late Early Cretaceous and late Paleocene. We carried out an integrated analysis from structural, 2-D and 3-D seismic data at the San Bernardo FTB and the adjacent Río Mayo Basin, studying sections of the Chubut Group Basin to unravel the different evolutionary stages. Thus, surface and subsurface evidence of syn-compressional deposition indicate the development of a broken foreland basin related to the formation of the San Bernardo FTB, suggesting an initial growth during the late Early Cretaceous and probably up to the late Paleocene. Our results imply that the Cretaceous compression acted in concert with transversal foreland extension. Hence, we propose a syncontractional rift reactivation of a potential lithospheric anisotropy, triggered by regional contraction. Finally, the origin of compression during this time is discussed in relation to multiple processes that go from high convergence between plates and trenchward motion of South America, collision of mid-ocean ridges, to potential dip changes in the subducted slab, as suggested by arc expansion.